SYNTACTIC CHARACTERISTICS OF POLYVALENT ELEMENTS IN ENGLISH AND UZBEK - Yeshboyeva Sevara Anvar qizi (TILSHUNOSLIKDA ANTROPOSENTRIZM: YANGI YONDASHUVLAR VA TADQIQOTLAR MAVZUSIDAGI RESPUBLIKA ILMIY-AMALIY ANJUMAN, 2026)
This research examines the syntactic characteristics of polyvalent elements in contemporary English and Uzbek, framed within modern linguistic theories. Polyvalence refers to a predicate's capacity to engage with multiple arguments. Employing a comparative approach, the study analyzes how English, an analytic language, conveys polyvalence through its fixed word order and specific syntactic frameworks, whereas Uzbek, being an agglutinative language, articulates syntactic relationships via case endings and morphological indicators. The findings reveal that while polyvalence is a universal linguistic occurrence, its syntactic manifestation differs markedly between languages. English features a configurational syntax system, in contrast to Uzbek's morphology-driven structure with greater flexibility in word order. The research also underscores that polyvalent constructions arise from the interplay of syntax, morphology, and semantics. Particular attention is paid to recent advancements in linguistic research, notably the contributions of Asadov, which broaden the comprehension of predicate valency by incorporating semantic and functional dimensions. The results enhance the field of comparative linguistics by showcasing language-specific expressions of polyvalence and emphasizing the necessity for integrating diverse theoretical frameworks in linguistic studies.